Lead poisoning in the Slimbridge wildfowl collection - Beer, J V; Stanley, P (Wildfowl, 1965)
Rather surprisingly, lead poisoning, following the ingestion of spent shot gun pellets, has been found to be an important cause of death among captive wildfowl at Slimbridge, Gloucestershire. Thirty-two species have been affected and the post-mortem findings are described. The source of the pellets has been investigated. The differential mortality among the various wildfowl tribes is possibly related to differences in feeding habits, diet and gritting as well as to susceptibility. Methods of prevention are discussed. Lead poisoning casualties have also been found in other collections in England.